THE EFFECT OF RELIGIOSITY, MUSLIM CUSTOMER PERCEIVED VALUE ON LOYALTY AND CUSTOMER SATISFACTION IN HALAL TOURISM IN INDONESIA (International Journal of Islamic Business, 2022)
The increase in the cumulative growth of international visitors to Indonesia between 2014 and 2018 compared to the preceding five-year period indicated that the tourism industry in Indonesia had promising growth potential. However, due to disruption in 2020 and 2021 during Pandemic period, the pre-pandemic projection of 230 million arrivals by 2026 will now be reached in 2028. This study aimed to examine the impact of the Muslim Customer Perceived Value (MCPV) on customer loyalty through customer satisfaction as an intervening variable among Muslims. In addition, study the impact of the religiosity of Muslim customers on customer satisfaction and loyalty among Muslims, as well as the impact of customer satisfaction on customer loyalty among Muslims. This study makes use of SEM (Structural Equation Modeling) for its analysis. According to the results of the investigation, various variables, including religiosity, and customer satisfaction have a strong positive effect on the variable of customer loyalty. However, there is no effect on the Muslim customer perceived value and the loyalty of Muslim customers.